A Cross-Comparison Study of Reentry Intervention and Support for Engagement: Findings on Youth With Disabilities. (May 2021) - Mathur, Sarup R.; Griller Clark, Heather; Gau, Jeff M.
This article presents the findings of a 2-year-long quasi-experimental study of post-release engagement and recidivism for youth with disabilities. The effects of specialized Reentry Intervention and Support for Engagement (RISE) for youth with disabilities were compared with two other groups: (a) youth with disabilities who received traditional special education services, and (b) youth without disabilities who received traditional general education services in a juvenile correctional facility. Regardless of group, participants who were engaged in the community 30 days post-release were more likely to be engaged at 120 days and less likely to recidivate than nonengaged participants. However, compared with the two other groups, participants who received RISE services were more likely to be engaged in the community at 120 days post-release and have significantly lower rates of recidivism. We conclude our study by examining limitations, suggestions, implications for practice and policy, and future research.